Responsibly shaping technology innovation for the energy transition: an RRI indicator system as a tool - Buchmann, Tobias; Wolf, Patrick; Müller, Matthias; Dreyer, Marion; Dratsdrummer, Frank; Witzel, Bianca (Frontiers in Research Metrics and Analytics, 2023)
Efforts to reduce global greenhouse gas emissions have had limited success. For many, the hopes rest on new energy innovations to advance the energy transition process. In this paper, we develop a Responsible Research and Innovation (RRI) base indicator system to steer the design of innovations in the field of energy transition innovations and, thus, improve social acceptance of these innovations. We propose a guideline for its application to assist R&D performing organizations and funding organizations in the design, selection, and communication of research proposals. The indicator system is intended to promote early integration of environmental and social aspects, support the formation of teams aware of the different responsibility aspects of innovation, and monitor progress in regard to relevant RRI dimensions.